2009
DOI: 10.1016/j.resp.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Time course of alterations in pre- and post-synaptic chemoreceptor function during developmental hyperoxia

Abstract: Postnatal hyperoxia exposure reduces the carotid body response to acute hypoxia and produces a long-lasting impairment of the ventilatory response to hypoxia. The present work investigated the time-course of pre- and post-synaptic alterations following exposure to hyperoxia (Fio2=0.6) for 1, 3, 5, 8 and 14 days (d) starting at postnatal day 7 (P7) as compared to age-matched controls. Hyperoxia exposure for 1d enhanced the nerve response and glomus cell calcium response to acute hypoxia, but exposure for 3-5d c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(72 citation statements)
references
References 46 publications
5
66
1
Order By: Relevance
“…As described for single-unit activity, this profound impairment of glomus cell [Ca 2+ ] i responses to acute hypoxia can be fully reversed after 7–8 days of recovery in normoxia (Bavis et al, 2011b). As expected for the blunted calcium response, hypoxia-induced vesicle release from glomus cells is similarly reduced by hyperoxia exposure (Donnelly et al, 2009). …”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…As described for single-unit activity, this profound impairment of glomus cell [Ca 2+ ] i responses to acute hypoxia can be fully reversed after 7–8 days of recovery in normoxia (Bavis et al, 2011b). As expected for the blunted calcium response, hypoxia-induced vesicle release from glomus cells is similarly reduced by hyperoxia exposure (Donnelly et al, 2009). …”
Section: Introductionsupporting
confidence: 59%
“…Although acute hypoxia generally raises intracellular calcium ([Ca 2+ ] i ) levels in glomus cells, the response is severely blunted by hyperoxia exposure. For instance, hyperoxia exposure of neonatal rats from P7 to P12 blunts the [Ca 2+ ] i response to acute hypoxia challenge and nearly abolishes the response when hyperoxia is continued to P14 (Donnelly et al, 2009). As described for single-unit activity, this profound impairment of glomus cell [Ca 2+ ] i responses to acute hypoxia can be fully reversed after 7–8 days of recovery in normoxia (Bavis et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Hyperoxia rats have smaller carotid bodies with fewer glomus cells and fewer chemoafferent neurons projecting to the brainstem (Erickson et al, 1998; Chavez-Valdez et al, 2012; Dmitrieff et al, 2012; Bavis et al, 2013). Futhermore, the remaining glomus cells are less sensitive to O 2 (Donnelly et al, 2005, 2009; Bavis et al, 2011b), and the spontaneous activity recorded from single-unit chemoafferent neurons may be reduced (or even silenced) at normoxic partial pressures of O 2 in Hyperoxia rats (Donnelly et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, week-old neonatal rats exposed to 60% O 2 for 23-28 hours exhibit reduced normoxic ventilation as well (Roeser et al, 2011). Previous studies have shown enhanced glomus cell O 2 sensitivity after 24-hour hyperoxic exposures in week-old rats (Donnelly et al, 2009), and it may take several days for hyperoxia to cause measurable changes to carotid body size (Dmitrieff et al, 2012). Thus, developmental hyperoxia likely influences normoxic ventilation by eliciting plasticity/injury at additional levels of the respiratory control system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation